Erratum to “An exponential random graph modeling approach to creating group-based representative whole-brain connectivity networks” [NeuroImage 60/2 (2012) 1117–1126] - Simpson, Sean L.; Moussa, Malaak N.; Laurienti, Paul J. (NeuroImage (Orlando, Fla.), 2012)
Note: "Distance" denotes the Euclidean distance between metric values of the potential representative networks and the corresponding mean or median metric values of the subjects' networks.